Sulfur addition acid balance method in biometallugical process - YONGSHENG SONG; RENMAN RUAN; JIANKANG WEN (2004)
An acid balance method by adding sulfur in biometallurgy features that in biological immersing extraction procedure of biometallurgy, the ore or concentrate of pyrite or sulfur, which can be oxidizedinto acid by extracting microbes, is mixed with the ore, concentrate, or tailings to be extracted. Its advantages are no need of supplementing sulfuric acid, optimal growth and reproduction of bacteria, low cost, and high extraction rate. 本发明公开了一种生物冶金过程中加硫的酸平衡方法，它是在生物冶金的生物浸出过程中，为维持浸出体系pH在1.0-2.5之间，在矿石或精矿或尾矿的生物浸出的准备工序中，配加能被浸矿微生物氧化成酸的黄铁矿的矿石或黄铁矿精矿或硫磺。本发明中采用添加能够被浸矿细菌所氧化，而且氧化产物之一是硫酸的含硫物质，该方法可以使含碱性矿物质丰富而金属硫化物少的矿石或精矿或尾矿，在细菌浸出时酸量得到平衡，生物浸出与产酸同时进行，产酸与耗酸同时进行，不需补加硫酸，药剂成本低，能够使细菌浸出程系统的pH值保持在细菌生长，繁殖的最佳状态，提高金属浸出率，缩短浸出周期，生产成本低。